Ultrahigh-speed graphene-based optical coherent receiver - Yilun Wang (Nature Portfolio, 2021)
Graphene-based photodetectors have many advantages for applications. Here, the authors demonstrate a high-speed optical coherent receiver for optical communications based on graphene-on-plasmonic slot waveguide photodetectors.